Effects of variable thermo-physical characteristics on MHD ternary hybrid second-grade nanofluid in rotating Jeffery-Hamel flow - Ibrahim Mahariq; Rania Saadeh; Farhan Lafta Rashid; Ahmad Qazza; Mohamed Kezzar; Hamiden Abd El-Wahed Khalifa; Mohamed Rafik Sari (International Journal of Thermofluids)
This research work presents the combined effect of variable electrical and thermal conductivity on the heat transfer of ternary hybrid nanofluids in second-grade flow between rotating non-parallel plates. Furthermore, this research work considers variables such as a rotating channel, non-linear solar radiation, sink/source conditions and the effects of stretching-shrinking walls. We examine a polymer-base fluid that contains hybrid nanoparticles. The fundamental equations undergo transformations from PDEs to ODEs through the use of similarity transformations. The Explicit Runge Kutta Method has numerically solved the computational problem; we validate the present findings in specific cases by comparing them with results from the HAM-based Mathematica package and literature references. We graphically display the impacts of physical factors on temperature, velocity, and engineering parameters. We also examine and demonstrate the impact of multiple variables on the engineering parameters. When it comes to improving heat transfer, this ternary hybrid nanofluid (THNF) does a much better job than the other nanofluids talked about in this research article. The results show that there is a big boost in thermal efficiency, especially when different flow rates are used.